2003
DOI: 10.1161/01.cir.0000066906.11109.1f
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Relation to Cardiovascular Disease and Total Mortality Among Men With Type 2 Diabetes

Abstract: Background-The present study was conducted to examine the relationship of physical activity with risk of cardiovascular disease (CVD) and mortality among men with type 2 diabetes. CVD risk and mortality are increased in type 2 diabetes. Few epidemiological studies have investigated the effect of physical activity on these outcomes among type 2 diabetics. Methods and Results-Of the 3058 men who reported a diagnosis of diabetes at age 30 years or older in the Health Professionals' Follow-up Study (HPFS), we excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
171
2
18

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(210 citation statements)
references
References 29 publications
17
171
2
18
Order By: Relevance
“…Our data on the protective effects of walking for all-cause and CVD mortality are consistent with recent literature (8)(9)(10)34,35). However, most previous studies have examined the effects of higher doses of walking.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our data on the protective effects of walking for all-cause and CVD mortality are consistent with recent literature (8)(9)(10)34,35). However, most previous studies have examined the effects of higher doses of walking.…”
Section: Resultssupporting
confidence: 91%
“…For example, in a previous study (9) individuals who walked $2 h/week had a 39% lower risk of all-cause mortality (22-52%) and a 44% lower risk of CVD mortality (4-55%) compared with those reporting no walking. Another study (10) found that diabetic patients classified in the top quintile ($16.1 MET-hours/week) of walking from a large U.S. cohort had a 43% lower risk of all-cause mortality (17-41%). Our results expand on these findings by suggesting that, even when other physical activity is taken into account, low doses of walking (0.1-5.3 MET-hours/week, corresponding roughly to 1.5-1.7 h of walking) were still beneficially associated with all-cause mortality among male patients with diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the present study, previous studies have shown that diabetes increases the risk of AMI [3][4][5], with a stronger association in women than in men [4,5], and that the most physically active people with diabetes have approximately half the risk of cardiovascular death compared with inactive people with diabetes [24,25]. Moreover, we have recently shown that physical activity modified the association between diabetes and mortality [26].…”
Section: Discussionsupporting
confidence: 89%
“…Endothelial function is a precocious marker of cardiovascular disease. But, although this study didn't evaluate long term issues, it is justified in the literature that intense exercise reduces cardiovascular risk [36][37][38][39] . Ostergard et al 40 is that the vascular function can improve at the beginning of the study and to begin a worsening after some weeks of intervention with exercise of high intensity, fact not noticed in our study, although with a time of intervention of six weeks.…”
Section: Limitationsmentioning
confidence: 99%